How young children learn independent asthma self-management: a qualitative study in Malaysia - Ramdzan, Siti Nurkamilla; Ee, Ming Khoo; Su, May Liew; Cunningham, Steve; Kendall, Marilyn; Sukri, Nursyuhada; Salim, Hani; Suhaimi, Julia; Lee, Ping Yein; Cheong, Ai Theng; Hussein, Norita; Hanafi, Nik Sherina Haidi; et al. (BMJ Publishing Group, 2020)
Objective We aimed to explore the views of Malaysian children with asthma and their parents to enhance understanding of early influences on development of self-management skills. Design This is a qualitative study conducted among children with asthma and their parents. We used purposive sampling and conducted focus groups and interviews using a semi-structured topic guide in the participants’ preferred language. All interviews were audio-recorded, transcribed verbatim, entered into NVivo and analysed using a grounded theory approach. Settings We identified children aged 7–12 years with parent-reported, physician-diagnosed asthma from seven suburban primary schools in Malaysia. Focus groups and interviews were conducted either at schools or a health centre. Results Ninety-nine participants (46 caregivers, 53 children) contributed to 24 focus groups and 6 individual interviews. Children mirrored their parents’ management of asthma but, in parallel, learnt and gained confidence to independently self-manage asthma from their own experiences and self-experimentation. Increasing independence was more apparent in children aged 10 years and above. Cultural norms and beliefs influenced children’s independence to self-manage asthma either directly or indirectly through their social network. External influences, for example, support from school and healthcare, also played a role in the transition. Conclusion Children learnt the skills to self manage asthma as early as 7 years old with growing independence from the age of 10 years. Healthcare professionals should use child-centred approach and involve schools to facilitate asthma self-management and support a smooth transition to independent self management.